Asset class diversification and delegation of responsibilities between central banks and sovereign wealth funds - Joshua Aizenman; Reuven Glick (University of California, Economics Department, 2010)
This paper presents a model comparing the optimal degree of asset class diversification abroad by a central bank and a sovereign wealth fund. We show that if the central bank manages its foreign asset holdings in order to meet balance of payments needs, particularly in reducing the probability of sudden stops in foreign capital inflows, it will place a high weight on holding safer foreign assets. In contrast, if the sovereign wealth fund, acting on behalf of the Treasury, maximizes the expected utility of a representative domestic agent, it will opt for relatively greater holding of more risky foreign assets. We also show how the diversification differences between the strategies of the bank and SWF is affected by the government's delegation of responsibilities and by various parameters of the economy, such as the volatility of equity returns and the total amount of public foreign assets available for management.
Keywords: E52; F15; F30; E58; 330; sovereign wealth funds; capital flows; foreign exchange reserves; financial markets; governance; Investmentfonds; Portfolio-Management; Zentralbank; Währungsreserven; Kapitalmobilität; Zahlungsbilanzgleichgewicht; Theorie